(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Conceptual metaphor theory plays an important role in understanding how language reflects human cognition. Media discourse frequently employs conceptual metaphors to frame social, political, and economic events. This article analyzes the isomorphic features of conceptual metaphors in English and Uzbek media texts. The study aims to identify similarities in metaphorical structures used in both languages despite cultural and linguistic differences. Using the theoretical framework of conceptual metaphor theory developed by George Lakoff and Mark Johnson, the research examines metaphorical expressions from English and Uzbek media sources. The findings show that many metaphors are structurally similar because they originate from universal human experience, such as movement, war, health, and construction.